2017
DOI: 10.1111/ejss.4_12398
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and soil functions

Abstract: Summary Soil is a complex and dynamic biological system, and still in 2003 it is difficult to determine the composition of microbial communities in soil. We are also limited in the determination of microbially mediated reactions because present assays for determining the overall rate of entire metabolic processes (such as respiration) or specific enzyme activities (such as urease, protease and phosphomonoesterase activity) do not allow any identification of the microbial species directly involved in the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(128 citation statements)
references
References 110 publications
3
104
0
10
Order By: Relevance
“…They exert negative influence on the biodiversity of valuable natural and extensively managed habitats (Zelnik 2012). These species are considered transformers (Tokarska-Guzik et al 2010), i.e., invasive species that Bchange the character, condition, form, or nature of ecosystems over a substantial area^ (Pyšek et al 2004); therefore, their effects on soil microbial processes and thus soil functioning (Nannipieri et al 2003) require detailed investigations. Previous research has been often conducted using either one or a small number of study sites, a single invasive species/ genus, and/or measuring few microbial properties, making generalizations on the impact of the invasion on soil functioning problematic Herr et al 2007;Scharfy et al 2009Scharfy et al , 2010Aguilera et al 2010;Dassonville et al 2011;Tharayil et al 2013;Mincheva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They exert negative influence on the biodiversity of valuable natural and extensively managed habitats (Zelnik 2012). These species are considered transformers (Tokarska-Guzik et al 2010), i.e., invasive species that Bchange the character, condition, form, or nature of ecosystems over a substantial area^ (Pyšek et al 2004); therefore, their effects on soil microbial processes and thus soil functioning (Nannipieri et al 2003) require detailed investigations. Previous research has been often conducted using either one or a small number of study sites, a single invasive species/ genus, and/or measuring few microbial properties, making generalizations on the impact of the invasion on soil functioning problematic Herr et al 2007;Scharfy et al 2009Scharfy et al , 2010Aguilera et al 2010;Dassonville et al 2011;Tharayil et al 2013;Mincheva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1) (100 g) -1 ). Due to the role of microorganisms in soil processes, their presence and biomass significantly affect the level of CO 2 emission from soils (Nannipieri et al, 2003), which is the result of root respiration and physiological processes of the microorganisms involved in the decomposition of organic material. Emissions of CO 2 from soils appear to be highly variable in heterogeneous soil micro-sites, and they are influenced by the activity of roots, microbial processes, crop residue and litter content, microclimate and catalytic properties of clay colloids (Matteucci et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Many papers suggested, that soil moisture and type of fertilization are key determinants of the microbial processes (Natywa et al, 2014), that determine the fluxes of GHG from soil (Nannipieri et al, 2003;Skiba et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is inferred that higher rates of N, P and K fertilization with organic carbon enhanced the activities of soil dehydrogenase activity. Nannipieri et al, (2003) reported that dehydrogenase activity reflects the oxidative activity or intensity of the metabolism of soil micro flora and can be used as an indicator of microbial activity.…”
Section: Dehydrogenase Activitymentioning
confidence: 99%